A Primer for Chiral Perturbation Theory - Scherer, Stefan; Schindler, Matthias R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Chiral Perturbation Theory, as effective field theory, is a commonly accepted and well established working tool, approximating quantum chromodynamics at energies well below typical hadron masses. This volume, based on a number of lectures and supplemented with additional material, provides a pedagogical introduction for graduate students and newcomers entering the field from related areas of nuclear and particle physics. Starting with the the Lagrangian of the strong interactions and general symmetry principles, the basic concepts of Chiral Perturbation Theory in the mesonic and baryonic sectors are developed. The application of these concepts is then illustrated with a number of examples. A large number of exercises (81, with complete solutions) are included to familiarize the reader with helpful calculational techniques.
Quantum Chromodynamics and Chiral Symmetry -- Spontaneous Symmetry Breaking and the Goldstone Theorem -- Chiral Perturbation Theory for Mesons -- Chiral Perturbation Theory for Bryons -- Applications and Outlook -- Pauli and Dirac Matrices -- Functionals and Local Functional Derivatives -- Solutions to Exercises -- Index.
Keywords: Physics; Law; Economics; Social sciences; Nanotechnology; Physics; Physics, general; Law, general; Nanotechnology; Social Sciences, general; R & D/Technology Policy